AN ANALYSIS OF POLITENESS AND IMPOLITENESS STRATEGIES USED IN ‘MIND YOUR LANGUAGE 1977’ SERIES - Lestiana, Fani; Syaputri, Komala Dwi (Lire Journal (Journal of Linguistics and Literature), 2025)
This study analyzed politeness and impoliteness strategies in the British sitcom Mind Your Language (1977), focusing on cross-cultural interactions within a multilingual classroom. Using Brown and Levinson’s (1987) politeness theory and Culpeper’s (2005) impoliteness framework, the research examined 13 episodes to identify how characters employed language strategies to maintain social harmony or assert dominance. The findings revealed that positive politeness was the most frequently used strategy, fostering group cohesion, while bald-on-record impoliteness occurred in authority-asserting situations. This study highlights the role of humor in shaping perceptions of politeness and impoliteness and demonstrates how cultural diversity influences communication styles. These insights contribute to the understanding of cross-cultural pragmatics and are valuable for linguists, educators, and media analysts. The research underscores the necessity of cultural awareness in multilingual interactions, suggesting implications for language teaching and intercultural competence development.